Beyond the “I” in the Obesity Epidemic: A Review of Social Relational and Network Interventions on Obesity - Janette S. Leroux; Spencer Moore; Laurette Dubé (Journal of Obesity)
Background. Recent research has shown the importance of networks in the spread of obesity. Yet, the translation of research on social networks and obesity into health promotion practice has been slow. Objectives. To review the types of obesity interventions targeting social relational factors. Methods. Six databases were searched in January 2013. A Boolean search was employed with the following sets of terms: (1) social dimensions: social capital, cohesion, collective efficacy, support, social networks, or trust; (2) intervention type: intervention, experiment, program, trial, or policy; and (3) obesity in the title or abstract. Titles and abstracts were reviewed. Articles were included if they described an obesity intervention with the social relational component central. Articles were assessed on the social relational factor(s) addressed, social ecological level(s) targeted, the intervention’s theoretical approach, and the conceptual placement of the social relational component in the intervention. Results. Database searches and final article screening yielded 30 articles. Findings suggested that (1) social support was most often targeted; (2) few interventions were beyond the individual level; (3) most interventions were framed on behaviour change theories; and (4) the social relational component tended to be conceptually ancillary to the intervention. Conclusions. Theoretically and practically, social networks remain marginal to current interventions addressing obesity.